Rancang Bangun Sistem Informasi Administrasi Kepegawaian Pada PT. Pancaran Semangat Jaya - Mawarizka Deviera; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2015)
PT. Pancaran Semangat Jaya is a company that moves in the field of Javanese magazine publishing named “Panjebar Semangat” which first published in 1933 until now. Currently, the administration of staffing is done by a subdivision of administration and documentation noted manually and the result is edited using Microsoft Word and Microsoft Excel applications, and then printed and stored in storage. This leads to a process of data search and check, as well as making the report which is reducing the working hour for the employees.Based on the problem, a solution is offered in the form of staffing administration information system that would connect the employees in every division inside the companies by using a dna-based client server and a waterfall method. This method uses sistematically approach and a serial ranging from the level of the needs of the system and heading to the stage of analysis, design, coding, testing and maintenance. The result of this research shows that the staffing administration information system may help PT. Pancaran Semangat Jaya to record and processing data by quickly and correctly. Moreover, that information system is in line with the needs of the company which has been proven by the outcome of the trial that has been implemented into eleven usual employees, three chief divisions, and one documentation administrative subdivision with the results of 82,7 % and included in a very well category.